FEATURES OF ORGANIZING CHILDREN AND ADOLESCENT TOURISM IN THE CITY OF AKTOBE - BOGENBAY, FARIZA (Вестник ЗКУ, 2023)
Annotation. The article mentions the organization of children and youth tourism in the vicinity of the city of Aktobe according to geographical features. Children's tourism is one of the most common types of tourism and performs educational, sanitary and other socially important functions. This is one of the most stable sectors of the tourist services market. The most developed and oldest directions of children's tourism in Kazakhstan are health and cultural-educational tourism, educational programs are always in demand. The article is devoted to the development of children's tourism in the current social space near the city of Aktobe. We have highlighted the prospects for the development of children's and youth tourism in the regions and the main directions of its improvement. For this, the market of children and youth tourism was studied, and the most popular types of recreation were determined. A survey of parents was conducted using Google Forms to explore the needs of children. The questionnaire consisted of 5 questions, as a result of which 96 people were asked and expressed their opinions. Formation and development of children's tourism depends on many factors: highly qualified specialist, suitable natural environment and location of historical and cultural heritage objects, funding, etc.It is clear that the economic growth in the field of children and youth tourism in Aktobe is limited by the lack of information transparency, orientation towards the provision of tourist services, which, in turn, contradicts the emerging opportunities of communication innovations that have significantly changed the conditions and opportunities for the implementation of interaction processes between people. Elements of socio-economic systems, which require diversification, affect a high level of income inequality.